Varljivo leto '68 . The Elusive Summer of '68 - Paskaljević, Goran (Centar Film Beograd, 1984)
Duration: 01:25:00 Set against the backdrop of a liberalization in Marshal Tito's Yugoslavia in 1968, this comedy is about the coming of age of Petar (Slavko Stimac) as he looks for love just about anywhere, now that he has discovered it exists. His father (Danilo Stojkovic) is a distant sort who wants him to focus on his grades so he will have a chance at a good future (and be a good Marxist), but Petar's card-shark of a grandfather understands and offers him the advice he needs. Meanwhile, Petar has a crush on his beautiful teacher and wreaks havoc with his academic standing by trying to get back at her for bathing in the river with her male companion. This affront to his feelings is soon forgotten when he meets a charming young miss who is visiting the town with a youth orchestra -- and love takes off from there. Reminiscent of the theme of budding adolescence in earlier films like "Black Peter" by Milos Forman or Jiri Menzel's "Closely Watched Trains," director Goran Paskaljevic shares his famous fellow Czechs' comic insight into the throes of first and uneasy love